Understanding restoration and transaction costs in a payment for ecosystem service water quality market in Oregon, USA - Kathleen Guillozet (VertigO)
In Oregon, USA, water temperature in many streams and rivers is a regulated condition that is being addressed in some contexts through a payment for ecosystem services (PES) approach. Through this approach, regulated utilities that discharge water into streams and rivers that is warmer than allowable are able to pay for riparian forest restoration and the cooling benefits that its shade brings in exchange for regulatory compliance. Mandatory water quality monitoring and reporting activities conducted by entities that make point source emissions provide the basis upon which an ecosystem service (riparian forest shade) is quantified (in kilocalories) and sold (per thermal credit). The City of Medford’s wastewater treatment facility in southern Oregon, USA, is the first regulated entity in Oregon to adopt a PES approach for regulatory compliance. Through analysis of verified trades and numerous other public documents, transaction costs associated with this program are estimated at 85 percent of total costs. Despite a growing literature on transaction costs in PES programs, there is little consensus or guidance on what is a reasonable percentage of total costs in order for PES programs to be deemed “efficient”. Regulators, permittees and the public can use this information to consider how to structure permits, what types of transaction costs are most or least important, and how to leverage investments for the greatest social, ecological and economic benefits.